2022
DOI: 10.1039/d2dt00127f
|View full text |Cite
|
Sign up to set email alerts
|

Formation of NiFe-MOF nanosheets on Fe foam to achieve advanced electrocatalytic oxygen evolution

Abstract: 2D bimetal metal organic frameworks (MOFs) are recognized as one of the most promising electrocatalysts for oxygen evolution reaction (OER). Herein, a facile approach was proposed to construct NiFe-MOF nanosheets...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…In recent years, iron foam (IF or FF) has also been a popular self-supported material for OER catalysis. [59][60][61] The reducing ability of iron is stronger than that of nickel, which helps to improve the reactivity of IF in the etching process. Moreover, iron is more abundant on earth and less costly than nickel, making it more conducive to large-scale production.…”
Section: Iron-based Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, iron foam (IF or FF) has also been a popular self-supported material for OER catalysis. [59][60][61] The reducing ability of iron is stronger than that of nickel, which helps to improve the reactivity of IF in the etching process. Moreover, iron is more abundant on earth and less costly than nickel, making it more conducive to large-scale production.…”
Section: Iron-based Electrocatalystsmentioning
confidence: 99%
“…In recent years, iron foam (IF or FF) has also been a popular self‐supported material for OER catalysis [59–61] . The reducing ability of iron is stronger than that of nickel, which helps to improve the reactivity of IF in the etching process.…”
Section: Principles and Applications Of Ltimentioning
confidence: 99%
“…Presently, NiFe-based MOFNAs have become popular OER electrocatalysts due to their outstanding structural characteristics and preeminent electrocatalytic performance. Duan et al grew a macroscale nanosheet array in situ (NiFe-MOFs/NF) with high flexibility on NF. Transmission electron microscopy (TEM) images showed that these nanosheets had clear lattice streaks with a lattice spacing of 1.4 nm.…”
Section: Mofnas Directly As Electrodes For the Oermentioning
confidence: 99%
“…[25][26][27] To further enhance the electrocatalytic performance of NiFe bimetallic electrodes, it is necessary to increase their specific surface area, which provides active surface sites. [28][29][30] At present, self-supporting nanomaterials are widely used as high surface area electrodes, 31,32 especially the ones with nanowires as structural units. [33][34][35][36] For instance, a self-supporting hierarchical nanowire array structure with abundant active sites was shown to enhance the bubble release and ion transfer.…”
Section: Introductionmentioning
confidence: 99%